Adverse Birth Outcomes among Hospital Deliveries in Pokhara Metropolitan - Acharya , Binita; Subedi, Bhawan; Yadav, Dipendra Kumar (One Health Journal of Nepal, 2024)
Introduction: Birth outcomes are a category of measures that describe health at birth. Adverse birth outcomes are other than normal live births, which majorly include preterm birth, stillbirth, and low birth weight. These are major causes of neonatal morbidity, mortality, and long-term physical and psychological issues. This study aimed to determine the proportion and identify the associated factors of adverse birth outcomes among hospital deliveries at Pokhara Metropolitan. ABSTRACT Methods: A cross-sectional analytical study was conducted in the selected hospitals of Pokhara Metropolitan among 258 admitted women in the maternity ward who had received delivery services within three days of delivery. Birth records of the newborn babies of the same respective mothers were taken and verified from hospital records. Initially, descriptive analysis was done to calculate the frequencies and then a chi-square test was done to identify the associated factors of adverse birth outcomes. Results: Out of 258 participants, 20.9 % of adverse birth outcomes were identified. Factors increasing the risk of adverse birth outcomes include poor knowledge of pregnancy or delivery complications, inadequate nutrition, lack of family support, previous adverse birth outcomes, history of miscarriage, tobacco use, and gestational age. Conclusions: The prevalence of the overall adverse birth outcome was more than one-fifth which is a public health concern. Adverse pregnancy outcome reduction strategies should consider early identification and management of the preconception risk factors. The preconception care should include educating all eligible or reproductive-aged couples about preconception care/ health. Creating awareness about family planning methods, types and efficacy for women of reproductive health is mandatory.